Intercultural Competence of Pre-Service Preschool Educators for the Globalized Community’s Requirements - Bondar, Tamara (Pedagogical Discourse, 2021)
The issue related to preservice preschool educators training in the USA and Ukraine has been explored. Research focused on defining the concept intercultural competence to distinguish its elements and their content. It also explored how intercultural competence evolved in the USA and came to be substituted by global competence focusing on the preparing globally competent workforce and cultural competence that is meant to be the core competence for educators dealing with the diverse population. The research studied how scholars defined the concept to describe the structure and content of cultural competence that could be useful for developing programs. It focuses on effective strategies that promote teaching cultural competence to preservice preschool educators. The research findings proved the importance of cultural competence for preservice preschool educators training in Ukraine. In the Preschool Educator professional standard in Ukraine cultural competence is included in the list of general competencies. The cultural competence is presented as the ability to show respect and appreciate Ukrainian culture, value diversity and multiculturalism; to be self-aware of national identity, and be able to express oneself creatively. As the standard does not include neither intercultural competence nor global competence, which are designed to teach skills for successful interaction in a globalized society, it is suggested that the cultural competence structure should be reconsidered redefined. It is advisable to extrapolate the American experience, which accumulates best practices in training highly qualified educators capable of working in a multicultural environment.